Stimulasi Brain Gym terhadap Perkembangan pada Anak Prasekolah - Nurun Ayati Khasanah; Ferilia Adiesti; Citra Adityarini Safitri; Sulis Diana (LPPM Akbid Harapan Ibu Pekalongan, 2022)
The incidence of general developmental delays is not known with certainty, but it is estimated that around 1-3% of children under the age of 5 years experience developmental delay disorders in general. WHO globally described 52.9 million children less than 5 years old, 54% of boys had developmental disorders in 2016. About 95% of children with developmental disorders live in low- and middle-income countries. One way to stimulate children is to use Brain Gym, which is a structured non-aerobic physical exercise intervention in which a combination of certain patterns of movement across the head, eyes, and extremities is performed along with brain and breathing exercises. Brain Gym routine performance results in stimulation and integration of various parts of the brain and motor skills in children. The implementation method is in the form of training with lecture and practical methods. The results showed an increase in the development of pre-school age children in Nurun Insani Kindergarten at the age of 5 and 6 years, namely 100%.